Ultra-thin films of amphiphilic lanthanide complexes: multi-colour emission from molecular monolayers - O'Neil AT; Harrison JA; Kitchen JA (Royal Society of Chemistry, 2021)
We report the synthesis and Langmuir-Blodgett deposition of 4 brightly emissive lanthanide amphiphiles that can be co-deposited to give multi-emissive ultra-thin films where two, three and four distinct lanthanide emission profiles are observed. To the best of our knowledge, this is the first report of a four-component emissive Langmuir-Blodgett film.